A Contemporary Evidence Synthesis of Leadership Styles and Their Impact on Organizational Performance: A Systematic Review - Reyes, Jon Paul; Malabanan, Manuel; Monterroyo, Carl Benedict (Journal of Interdisciplinary Perspectives, 2025)
This systematic review examined the relationship between various leadership styles and organizational performance, drawing on 42 studies published between 2019 and 2025. Although extensive research exists, the literature remains fragmented due to inconsistent contexts, overlapping constructs, and diverse performance indicators. The review aimed to (1) determine which leadership styles are most strongly linked to performance outcomes, (2) identify mediating and moderating factors that shape this relationship, and (3) highlight gaps for future research. Guided by the PRISMA 2020 framework, relevant studies were systematically gathered from Scopus, Web of Science, ScienceDirect, Emerald Insight, and Google Scholar. A narrative synthesis approach was used to integrate both quantitative and qualitative evidence. Findings revealed that transformational leadership most consistently enhances innovation, employee engagement, and long-term organizational performance. Transactional leadership contributes to short-term efficiency and goal attainment, while servant leadership fosters ethical cultures and supports employee well-being. Emerging models, remarkably adaptive and distributed leadership, are gaining prominence in post-pandemic and digital work environments. The results also indicate that leadership effectiveness is context-dependent, with cultural and sector-specific differences influencing outcomes. Overall, the review concludes that no single leadership style universally guarantees organizational success. Instead, a blended approach incorporating transformational, servant, and adaptive elements appears most effective in promoting resilience and sustainable performance. These insights offer valuable implications for leadership development, organizational policy, and innovation strategies in rapidly evolving environments.